Mechanistic assessment of aerosol transport in SFR cover gas space post HCDA conditions - Patel, Parthkumar Rajendrabhai; Kumar, Amit; Arul, A. John (Frontiers in Nuclear Engineering, 2025)
With the growing emphasis on safety in next-generation reactors, along with the necessity to practically eliminate large doses to the public from severe accidents, a mechanistic assessment of such accidents becomes very important problem. The present manuscript attempts to address the source term assessment, focusing on the release behaviour of the aerosol from the roof-slab leak paths post-Core Disruptive Accident (CDA) conditions (known as interface source term or cover gas source term). Following a CDA, after possible Na leak through the gap between rotating plugs and major components, the cover gas space could be in contact with the containment atmosphere through these open leak paths. Additionally, the impact of sodium slug to roof-slab could have caused roof-slab cooling line failure. The present study assesses the release behaviour of the aerosols from the roof-slab leak paths, with respect to aerosol size under various cases of roof-slab cooling line failure. Sodium aerosols are used as representative aerosols for studying the radionuclide (RN) aerosol release behaviour. The assessment indicates that most of the aerosol leaking from roof-slab leak paths are of the diameter between 5 and 25 μm, with leak rates peaking in the range of 17–23 μm. Furthermore, with respect to air ingress concern, it is observed that the air ingress from the containment atmosphere was found only in the annular leak paths and it is not mixing into cover gas. However, this ingress was limited to the annular leak path only. It is seen that higher leak rates are observed in the case of complete failure of the roof-slab cooling system. Hence, it is important to maintain the roof-slab bottom plate temperatures within limits to avoid larger aerosol leak rates.